Highly selective Pd composite membrane on porous metal support for high-purity hydrogen production through effective ammonia decomposition. (1st December 2022) - Kim, Tae-Woo; Lee, Eun-Han; Byun, Segi; Seo, Doo-Won; Hwang, Hyo-Jung; Yoon, Hyung-Chul; Kim, Hansung; Ryi, Shin-Kun
Abstract: In this study, an alumina sol assisted pretreatment method for porous metal supports was investigated for a highly selective Pd composite membrane for ammonia decomposition. Alumina sol made of boehmite was applied to an yttria-stabilized zirconia (YSZ) filled porous Inconel support. Additionally, a vacuum-assisted, two-step electroless plating of Pd drastically increased the hydrogen selectivity. The hydrogen permeation flux and selectivity (H2 /N2 ) measured at 723 K and a transmembrane pressure difference of 100 kPa were 3.40 × 10 −1 mol m −2 s −1 and 8, 050, respectively. A highly selective Pd composite membrane was applied to a membrane reactor combined with a Ru/Al2 O3 catalyst to efficiently produce high-purity hydrogen by ammonia decomposition. The ammonia decomposition test showed that the membrane reactor was able to achieve a high ammonia conversion (99.6%) and a high hydrogen purity (99.99%) with a hydrogen production rate of 0.25 Nm 3 h −1 at 745 K and a gauge pressure of 500 kPa. The Pd composite membrane reactor has the advantage of being able to selectively removing hydrogen, increasing the ammonia conversion rate and high-purity hydrogen production via a one-step reaction combined with purification. Graphical abstract: Image 1 Highlights: Alumina sol treatment increased perm-selectivity of a Pd based composite membrane. Ammonia decomposition test was carried out by using the highly selective membrane. Ammonia decomposition showed 99.6% conversion rate at 745 K and gauge pressure of 500 kPa. H2 recovery ratio of 87% and H2 production rate of 0.25 Nm 3 h −1 with 99.99% purity was obtained.